Eleven minutes - Coelho, Paulo (Thorsons, an imprint of HarperCollins Publishers, 2014)
Eleven Minutes is the story of Maria, a young girl from a Brazilian village, whose first innocent brushes with love leave her heartbroken. At a tender age, she becomes convinced that she will never find true love, instead believing that "love is a terrible thing that will make you suffer. . . ." A chance meeting in Rio takes her to Geneva, where she dreams of finding fame and fortune. Maria's despairing view of love is put to the test when she meets a handsome young painter. In this odyssey of self-discovery, Maria has to choose between pursuing a path of darkness -- sexual pleasure for its own sake -- or risking everything to find her own "inner light" and the possibility of sacred sex, sex in the context of love.